STUDI DESKRIPTIF TINGKAT KEPUASAN PENGGUNA TRANSPORTASI BERBASIS ONLINE - Vivi Sahfitri (Direktorat Riset dan Pengabdian Pada Masyarakat (DRPM) Universitas Bina Darma, 2020)
This study aims to conduct a descriptive study of the level satisfaction online-based transportation users viewed based on the perception by users of online transportation services. Measuring the level of satisfaction of users of online transportation services using the ServQual method provided by the driver to service users by using the variables Reliabiilty, Responsiveness, Assurance, Empathy and Tangibles. Based on the results of the study, it can be known that in each variable measured more than 50% of respondents responded to the good category of statements given related to the quality of service to users. In addition, the conclusion that can be obtained based on the results of the study is the average value of measurement shows the level of satisfaction in the category of satisfied with the quality of driver service in online-based transportation services.